Can good ESG performance help companies resist external shocks? - Yang, Xin; Sheikh Hassan, Ahmad Fahmi; Karbhari, Yusuf (Taylor and Francis, 2024)
In order to validate the varied conclusions regarding the integration of corporate ESG practices by investors during external shocks, this study utilises the COVID-19 crisis as a specific external shock. The findings from our difference-in-differences methodology suggest that companies demonstrating strong ESG performance have succeeded in reducing idiosyncratic risk throughout the pandemic period. Additionally, we uncover that revenue growth acts as a critical pathway through which ESG performance reduces firm-specific risk, highlighting that firms with strong ESG practices achieved higher revenue growth, which in turn contributed to risk reduction. Further analysis shows that the political environment and dividend policy influence this relationship, as examined through heterogeneity analysis. By employing the quantile difference-in-difference technique in conjunction with the adaptive Markov Chain Monte Carlo method, we depict the dynamic evolution track of the marginal effect of ESG performance across various levels of idiosyncratic risk. Our results remain robust even after a series of rigorous robustness checks.